Roman Catholic Cathedral, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (James Book Store, 2010)
This is a frontal view of the Roman Catholic Cathedral named the Cathedral of the Immaculate Conception, Port of Spain, Trinidad and Tobago. This Cathedral replaced the first Catholic Church ever built in Port of Spain. The first church was built of wood and clay 1781 on the site that is now Tamarind Square. The foundation stone for the Cathedral of the Immaculate Conception was laid in March 1816 west of Tamarind Square, on the eastern end of Marine Square, now called Independence Square. The church was consecrated 1832, completed in 1936 and in 1851 was ranked a Minor Basilica. One of the unique features of the Cathedral is a crypt beneath the building that houses the final remains of Catholic Church officials, including Archbishops interred here from 1828 to 2000. Postcard number 29.
Colour: White, Blue, Rust, Grey, Green and Cream Hues; Style: Portrait; Other: Unbordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Catholic Church--Trinidad and Tobago; Church buildings--Trinidad and Tobago; Christianity--Trinidad and Tobago; Catholics--Trinidad and Tobago; Catholic church buildings--Trinidad and Tobago; Church architecture--Trinidad and Tobago; Architecture--Details; Cathedrals--Trinidad and Tobago; Clocks and watches--Trinidad and Tobago; Towers--Trinidad and Tobago; Palms--Trinidad and Tobago; Shrubs--Trinidad and Tobago; Gates--Trinidad and Tobago; Fences--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; [1905]; Marine Square (Port of Spain); Independence Square (Port of Spain)